THE EFFECT OF ROSEMARY ESSENTIAL OIL (ROSMARINUS OFFICINALIS L.) ON IMPROVING SHORT-TERM MEMORY IN ELDERLY PEOPLE - Bulain, Jessica Julia; Suyono, Handi; Supit, Paulus Alexander (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
Memory is the human ability to receive and store information. With increasing age, the brain's work function will also experience a decline, which will have an impact on individual cognitive function. Memory decline is a common thing that occurs in people of older age. Rosemary essential oil is one of the additional therapies that are useful in improving working memory and short-term memory. This study aims to determine the effect of rosemary essential oil on short-term memory in elderly people. This research is quasi-experimental with group control, with data collection techniques, namely, random sampling. The research was measured using the digit span test as a short-term memory test involving 32 elderly respondents with an age range of 65-85 years. This research was conducted by administering rosemary essential oil to the treatment group and jojoba oil to the control group by inhalation using a mask for 7 days in the morning, with the results of the pretest and posttest comparison between the two groups then analyzed using the Wilcoxon test. The results obtained from the study were that there was a significant value in the experiment group given rosemary essential oil, namely with a p-value of (p<0.005), which means that there is an influence between rosemary essential oil and short-term memory.